Does ozone administration have a protective or therapeutic effect against radiotherapy-induced testicular injury - Aydogdu, Ibrahim; AYDOĞDU, İBRAHİM; Ilbey, YUSUF ÖZLEM; İLBEY, YUSUF ÖZLEM; ÇOBAN, GANİME; ÇOBAN, GANİME; Ekin, Rahmi Gokhan; Mirapoglu, Semih Lutfi; MİRAPOĞLU, SEMİH LÜTFİ; Cay, Ali; ÇAY, ALI; Kiziltan, Huriye Senay; et al. (My University, 2019)
Objective: We investigate the protective and therapeutic effects of ozone therapy (OT) in radiotherapy (RT)-induced testicular damage. Methods: Thirty healthy adult male Wistar rats divided into five groups consisting of six animals each as follows: (1) Control (C), (2) RT, (3) OT, (4) OT + RT, and (5) RT + OT group. Histopathological findings, Johnsen scores, thiobarbituric acid-reactive substances (TBARS), glutathione (GSH), superoxide dismutase (SOD), catalase, and glutathione peroxidase (GPx) levels were evaluated. Results: RT caused a significant decrease in testicular weight and Johnsen score compared to the control group. In addition, TBARS level was significantly higher, whereas GSH, SOD, catalase, and GPx levels were significantly lower in the RT group when compared to the control group. Pre and postRT OT significantly increased GSH, SOD, catalase, and GPx levels and decreased TBARS level. Furthermore, testicular weight and Johnsen score were increased with OT. Conclusions: The present study showed that OT is protective and therapeutic in radiation-induced testicular damage. OT may be beneficial to the patients who underwent RT.